Health‐Related Quality of Life in an Inception Cohort of Children With Juvenile Idiopathic Arthritis: A Longitudinal Analysis. Issue 1 (6th December 2017) - Oen, Kiem; Guzman, Jaime; Dufault, Brenden; Tucker, Lori B.; Shiff, Natalie J.; Duffy, Karen Watanabe; Lee, Jennifer J. Y.; Feldman, Brian M.; Berard, Roberta A.; Dancey, Paul; Huber, Adam M.; Scuccimarri, Rosie; et al.
Abstract : Objective: To describe changes in health‐related quality of life (HRQoL) over time in children with juvenile idiopathic arthritis (JIA), relative to other outcomes, and to identify predictors of unfavorable HRQoL trajectories. Methods: Children with JIA in the Research in Arthritis in Canadian Children emphasizing Outcomes (ReACCh‐Out) cohort were included. The Juvenile Arthritis Quality of Life Questionnaire (JAQQ, a standardized instrument), health‐related Quality of My Life (HRQoML, an instrument based on personal valuations), and JIA core variables were completed serially. Analyses included median values, Kaplan‐Meier survival curves, and latent trajectory analysis. Results: A total of 1, 249 patients enrolled at a median of 0.5 months after diagnosis were followed for a median of 34.2 months. The degree of initial HRQoL impairment and probabilities of reaching the best possible HRQoL scores varied across JIA categories (best for oligoarthritis, worst for rheumatoid factor–positive polyarthritis). Median times to attain best possible HRQoL scores (JAQQ 59.3 months, HRQoML 34.5 months), lagged behind those for disease activity, pain, and disability measures. Most patients followed trajectories with minimal or mild impairment; however, 7.6% and 13.8% of patients, respectively, followed JAQQ and HRQoML trajectories with persistent major impairment in HRQoL. JIA category, aboriginal ethnicity, and baseline disease activity measures distinguished between membership in trajectories with major and minimal impairments. Conclusion: Improvement in HRQoL is slower than for disease activity, pain, and disability. Improvement of a measure based on respondents' preferences (HRQoML) is more rapid than that of a standardized measure (JAQQ). Higher disease activity at diagnosis heralds an unfavorable HRQoL trajectory.